The United Methodist Church a study of the information flow of its projects, programs and activities - Rivera, Mercidita F. (Institute of Library Science, University of the Philippines Diliman, 2001)
The existing communication system in the United Methodist Church (UMC) of the Quezon City District (Philippines) is seen to be unable to cope effectively and effeciently with the information and communication needs of its brethren. It had led in the past to the poor implementation of its programs, projects and activities. This study looked at the nature of the problem through a survey of a stratified sample of 497 drawn from the Church hierarchy--from the top leadership down to the parishioners.